2012
DOI: 10.1071/sr11152
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen loss by surface runoff from different cropping systems

Abstract: Reducing nitrogen (N) loss from agricultural soils as surface runoff is essential to prevent surface water contamination. The objective of 3-year study, 2007–09, was to evaluate surface runoff and N loss from different cropping systems. There were four treatments, including one single-crop cropping system with winter wheat (Triticum aestivum L.) followed by summer fallow (wheat/fallow), and three double-cropping systems: winter wheat/corn (Zea mays L.), wheat/cotton (Gossypium hirsutum L.), and wheat/soybean (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
1
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 32 publications
0
4
1
1
Order By: Relevance
“…In addition, rice and maize are produced using relatively high levels of nitrogen fertilizer and pesticides (NASS, 2013a(NASS, , 2015. Excessive irrigation has potential to convey contaminants into waterbodies via surface runoff and/or deep-percolation losses (Aryal and Reba, 2017;Baker et al, 2018;Jiao et al, 2012;King et al, 2018). Hence, improvements in IWM are expected to help reduce nonpoint-source pollution as well as improve farm productivity.…”
Section: Innovations In Crop Managementmentioning
confidence: 99%
“…In addition, rice and maize are produced using relatively high levels of nitrogen fertilizer and pesticides (NASS, 2013a(NASS, , 2015. Excessive irrigation has potential to convey contaminants into waterbodies via surface runoff and/or deep-percolation losses (Aryal and Reba, 2017;Baker et al, 2018;Jiao et al, 2012;King et al, 2018). Hence, improvements in IWM are expected to help reduce nonpoint-source pollution as well as improve farm productivity.…”
Section: Innovations In Crop Managementmentioning
confidence: 99%
“…Jiao et al (2012) produced a similar finding, but our results disagree with Zhang et al (2010), who did not found significant differences in mineral nitrogen losses between bare soil and two levels of covered soil. As expected, T was the treatment with the higher nitrate loss, since it was the soil management with significantly higher NO 3 soil.…”
Section: Discussioncontrasting
confidence: 57%
“…GC acted as catch crops in arable cover crops and caught the soil nitrate creating organic biomass (Gabriel and Quemada, 2011;Gabriel et al, 2013;Gabriel et al, 2012). Consequently, T induced higher runoff rates, and runoff mineral nitrogen concentration was higher (Jiao et al, 2012). These concentrations were especially higher during the first minutes of the experiments, which encourage the need of increase infiltration rates and avoid runoff events.…”
Section: Gc Influence On Runoff and Mineral Nitrogen Lossmentioning
confidence: 95%
“…Pupuk slow release adalah salah satu alternatif teknologi untuk meningkatkan efisiensi pemupukan. Unsur N dapat hilang melalui volatilisasi ammonia, proses nitrifikasi, denitrifikasi mikrobial, pencucian dan hilang melalui runoff (Chichester et al 1992;Choudhury et al 2005;Jiao et al 2012;Fang et al 2015). Terdapat bermacam jenis pupuk slow release yang sudah di produksi dan tersedia di pasar yaitu Urea granul, Urea tablet, Urea coated silika, Urea coated sulfur (Peoples et al 1995;Shoji et al 1995;Shaviv 2000).…”
Section: Pendahuluanunclassified